Embolism microsphere with negative charges and preparation process of embolism microsphere

High elastic embolization microspheres prepared by reverse phase suspension cross-linking method use the cross-linking reaction between hydrophilic polyhydroxy polymer and polyate ionic polymer to solve the mutual connection between existing microsphere drug carrying capacity and compression elasticity. It restricts the problem and achieves efficient drug adsorption and sustained release effects, which are suitable for embolization treatment that penetrates into the blood vessels.

CN119424717APending Publication Date: 2025-02-14ZHUHAI HUAHAIKANG MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310965143.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing embolizing microspheres have problems of mutual constraints in drug carrying capacity and compression elasticity, and are prone to problems such as coagulation, irregular deformation and excessive drug release speed during the preparation process.

Method used

Highly elastic embolized microspheres were prepared by reverse phase suspension cross-linking method, and the cross-linking reaction of hydrophilic polyhydroxy polymers with polymers containing polyate ions was used to form negatively charged microspheres, which improved drug adsorption capacity and relaxed Release the effect.

Benefits of technology

It realizes the high drug loading ability, rapid adsorption and sustained release of microspheres, with excellent compressibility and elasticity, and is suitable for embolization treatment in deep blood vessels, and maintains stability for a long time during drug release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424717A_ABST
    Figure CN119424717A_ABST
Patent Text Reader

Abstract

The invention relates to an embolism microsphere and a preparation method thereof, and belongs to the field of medical interventional therapy. Polyvinyl alcohol is adopted as a base material and is cross-linked with a cross-linking agent to generate microspheres, and meanwhile, a polymer material containing polyacid radical ions is introduced. The modified microspheres prepared by the method have the same regular spherical shape as that of unmodified polyvinyl alcohol, and are controllable in size and good in suspension property and deformation elasticity. Meanwhile, due to the introduction of functional groups with negative charges, the microspheres can be combined with micromolecular antitumor drugs with positive charges, so that the microspheres have very good drug loading performance. The preparation process is a pure chemical synthesis process, the raw materials and the preparation process are free of virus pollution, various requirements of international embolism agents are met, various imported and domestic expensive embolism agent products can be replaced, and the method can be widely applied to various operations in the field of interventional therapy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an embolic microsphere which can be used for interventional surgery to treat tumor diseases and a preparation process thereof, and belongs to the field of medical devices. Background Art

[0002] Interventional therapy is a treatment method that combines imaging diagnosis and clinical treatment. It entered clinical application after rapid development in the 1970s. Interventional therapy is based on imaging diagnosis. It uses catheters and guide wires through percutaneous puncture technology to treat local lesions of patients with drugs, vasodilation or vascular embolization, etc., which reduces the wound and pain of patients, has better local efficacy of drugs, and reduces systemic side effects of drugs. It is simpler, more effective and more direct than traditional surgical methods.

[0003] Embolization is a treatment method that blocks or slows the blood supply to a tissue or organ. It can be used to block blood flow from the arteries to the tumor, causing cancer cells to be ischemic and die due to lack of nutrients. When the material used to block the blood supply also delivers chemotherapy drugs to the tumor, it is called chemoembolization. Among them, transcatheter arterial chemoembolization (TACE) is a special type of local chemoembolization that can block the hepatic artery to achieve the effect of treating unresectable or metastatic hepatocellular carcinoma (HCC). HCC is the most common type of primary liver cancer. This type of tumor grows a large number of blood vessels and most of the blood supply of these blood vessels comes from the hepatic artery, while the rest of the liver tissue comes from the portal vein. Therefore, the blood supply to the tumor can be cut off by blocking the hepatic artery without affecting the rest of the liver.

[0004] The embolic materials available on the market are mainly divided into liquid embolic materials and solid embolic materials. Among them, liquid embolic materials have been increasingly replaced by solid embolic materials due to their fluidity, which leads to unstable embolism and inability to play a sustained release role when combined with chemotherapy drugs for embolization. As a commonly used embolic agent in clinical practice, the product development of solid embolic materials has undergone the following evolution: the first generation is irregularly shaped gelatin sponges and polyvinyl alcohol particles. Due to their irregular shapes, they are easy to aggregate and difficult to push in clinical use, and the embolization of blood vessels is not thorough enough; the second generation is spherical blank microspheres with uniform size, such as polyvinyl alcohol blank microspheres and sodium alginate microspheres. This type of embolic microspheres has regular shapes and uniform particle sizes. At the same time, they can adapt to the shape of blood vessels and embolize blood vessels thoroughly; the third generation of embolic microspheres are drug-loaded embolic microspheres, which not only have the characteristics of regular shape and uniform particle size, but also have certain elasticity and compression deformation ability, and can reach deeper tumor blood vessels through microcatheters for more accurate embolization. At the same time, it also has the ability to carry drugs. The adsorbed drugs can be slowly released locally at the lesion, significantly increasing the concentration of the drugs in the local liver cells and improving the therapeutic effect of the drugs.

[0005] Among the embolic material products currently on the market, the products that can encapsulate chemotherapy drugs include DCBead from the British Biocompatibles Company, Hepasphere from the American BioSphere Company, and CalliSpheres under the Hengrui Group. The above three types of microspheres all use polyvinyl alcohol polymer materials as the main materials of the microspheres. By modifying polyvinyl alcohol, high molecular monomers with double bonds are grafted on its molecular chain, and the high molecular monomers are polymerized and cross-linked with monomers with ionic functional groups to form charged embolic microspheres, thereby realizing the drug-carrying function. This type of embolic microsphere has a certain drug-carrying capacity and compression elasticity, but because it is achieved by the polymerization of polyvinyl alcohol grafted monomers with ionic functional groups, the more polyvinyl alcohol grafted monomers, the more ionic functional groups the microspheres contain, and the stronger its drug-carrying capacity, but at the same time, the higher the cross-linking degree of the polyvinyl alcohol microspheres, the worse the compressible elasticity of the microspheres, and the worse the expansion performance and drug-carrying speed of the microspheres. This mutual restriction limits the optimization of the drug-carrying performance and compression elasticity of the embolic microspheres. In addition, there are literature reports that in the process of preparing these ion exchange microspheres, the high viscosity of polyvinyl alcohol may cause the microspheres to aggregate during the polymerization process. In addition, there are also occasional phenomena such as irregular spherical shapes when the microspheres are mixed with aqueous solutions for too long, and the drug release system releases chemotherapy drugs faster in the blood vessels. Therefore, new synthesis methods and microsphere structural characteristics are needed to achieve chemoembolization with more ideal performance. Summary of the invention

[0006] The present invention provides a simple, industrially scalable preparation process for highly elastic embolic microspheres prepared by cross-linking reaction. The microspheres are characterized by mainly adsorbing cationic drugs or molecules inside and outside the spheres, thereby improving the drug or molecule adsorption capacity and accelerating the adsorption speed. At the same time, the microspheres prepared by the reverse suspension cross-linking method have a small density inside and a large density outside, which makes the compressibility better and helps the internal water absorption and expansion capacity. The method requires simultaneous regulation of the following steps:

[0007] 1. Adjust the ratio of hydrophilic polyhydroxy polymer material to polymer material containing polyacid ions so that the microspheres contain a certain proportion of hydroxyl groups and acid radicals, which have a strong adsorption effect on positively charged drug molecules. Too much hydrophilic polyhydroxy polymer material will weaken the adsorption capacity of drug molecules, and too little hydrophilic polyhydroxy polymer material will affect cross-linking into spheres.

[0008] 2. Adjust the molar ratio of the cross-linking agent to the hydrophilic polyhydroxy polymer so that the hydrophilic polyhydroxy polymer material in the microspheres maintains a certain degree of cross-linking and can fully entangle the polyacid ion polymer material to form regular, elastic and compressible microspheres. Too much cross-linking agent will cause excessive cross-linking of the microspheres, thereby reducing the elasticity and compressibility of the microspheres. Too little cross-linking agent will result in the inability to form microspheres or a large number of broken microspheres.

[0009] 3. Adjust the volume ratio of water in the aqueous phase and the organic solvent in the oil phase, control the uniform dispersion of the aqueous phase droplets in the oil phase, and control the appearance morphology and particle size of the microspheres.

[0010] 4. The water content of the microspheres prepared by the above process is between 90% and 97%, so that the microspheres have good flexibility, which can be used to embolize the irregularly shaped blood vessel ends and obtain a better embolization effect.

[0011] Therefore, in view of the above technical problems, the purpose of the present invention is to provide a method for preparing negatively charged embolic microspheres. The present invention also aims to provide negatively charged embolic microspheres, which have uniform particle size and strong adsorption effect on positively charged drugs.

[0012] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0013] The invention discloses an embolic microsphere with adsorption capacity, which is prepared by an inverse emulsion method (W / O). The embolic microsphere is formed by a biocompatible polymer material reacting with a cross-linking agent to form a network structure, and the microspheres are mutually entangled to form regular elastic microspheres with negative charges.

[0014] A method for preparing negatively charged embolic microspheres comprises the following steps:

[0015] A) dissolving a hydrophilic polyhydroxy polymer and a polymer containing polyacid ions in water, stirring uniformly, to obtain an aqueous phase;

[0016] B) dissolving the dispersant in an organic solvent and stirring the mixture to obtain an oil phase;

[0017] C) adding the aqueous phase to the oil phase for dispersion to obtain a mixed emulsion, adding a crosslinking agent to the mixed emulsion once or several times and stirring to obtain microspheres;

[0018] D) washing and filtering the microspheres obtained in step C),

[0019] After the aqueous phase is prepared in step A) or after the mixed emulsion is obtained in step C), the pH is adjusted to be acidic.

[0020] Preferably, the molar ratio of the hydrophilic polyhydroxy polymer to the polymer containing polyacid ions is 0.8:1 to 12:1.

[0021] More preferably, the molar ratio of the hydrophilic polyhydroxy polymer to the polymer containing polyacid ions is 2.3:1 to 12:1.

[0022] Preferably, the total weight of the hydrophilic polyhydroxy polymer and the polymer containing polyacid ions accounts for 4% to 15% of the total weight of the aqueous phase. The calculation formula is:

[0023] The mass percentage of the total weight of the hydrophilic polyhydroxy polymer and the polymer containing polyacid ions to the total weight of the aqueous phase = (weight of the hydrophilic polyhydroxy polymer + weight of the polymer containing polyacid ions) / (weight of the hydrophilic polyhydroxy polymer + weight of the polymer containing polyacid ions + weight of water) * 100%

[0024] Preferably, the molar ratio of the crosslinking agent to the hydrophilic polyhydroxy polymer is 1:4 to 1:19.

[0025] Preferably, the volume ratio of water in the aqueous phase to the organic solvent in the oil phase is 1:1.5 to 1:20.

[0026] Preferably, the organic solvent for preparing the oil phase is one or more of organic solvents such as butyl acetate, ethyl acetate, and n-heptane.

[0027] Preferably, the mass percentage of the dispersant in the oil phase is 0.8% to 5.0%, calculated as follows:

[0028] The mass percentage of dispersant in the oil phase = mass of dispersant / (mass of dispersant+mass of organic solvent)*100%.

[0029] Preferably, the hydrophilic polyhydroxy polymer is polyvinyl alcohol (PVA) with a molecular weight of 20 to 600 kilodaltons.

[0030] Preferably, the polyacid ion polymer is a polymer containing polycarboxyl functional groups and / or a polymer containing polysulfonic functional groups. Further preferably, the polymer containing polycarboxyl functional groups is polyacrylic acid and / or its salt, polymethacrylic acid and / or its salt, and the polymer containing polysulfonic functional groups is polystyrene sulfonic acid and / or its salt, polyethylene sulfonic acid and / or its salt. Further preferably, the polymer containing polycarboxyl functional groups is one or more of sodium polyacrylate (PAANa), partially neutralized sodium polyacrylate, polyacrylic acid (PAA), sodium polymethacrylate and polymethacrylic acid, each of which has a molecular weight of 10 to 600 kilodaltons, wherein the mass ratio of acrylic acid to sodium acrylate in the partially neutralized sodium polyacrylate is 2:8 to 8:2; the polymer containing polysulfonic functional groups is one or more of sodium polystyrene sulfonate, polystyrene sulfonic acid, sodium polyethylene sulfonate and polyethylene sulfonic acid, each of which has a molecular weight of 20 to 2000 kilodaltons.

[0031] Preferably, the cross-linking agent is an aldehyde compound, and more preferably, the cross-linking agent is glyoxal and / or glutaraldehyde.

[0032] Preferably, the dispersant is one or a combination of Span 80, Tween 80, cellulose acetate and cellulose acetate butyrate.

[0033] Preferably, in step C), the aqueous phase is dispersed in the oil phase using shearing or stirring equipment, wherein the stirring speed is 50 rpm to 1000 rpm.

[0034] Preferably, after the aqueous phase is prepared in step A) or after the mixed emulsion is obtained in step C), one or more of hydrochloric acid, sulfuric acid and acetic acid are added to adjust the pH to 3-5; the microspheres collected by filtration in step D) are washed with butyl acetate and ethyl acetate in sequence, and then washed with acetone or ethanol, and then vacuum dried to obtain dry microspheres, the dry microspheres are soaked in pure water and filtered, then soaked in sodium hydroxide solution and filtered with water, and then filtered, sieved and collected after stirring in boiling water.

[0035] As another aspect of the present invention, there is also provided a negatively charged hydroxyl cross-linked embolic microsphere prepared according to any one of the above methods.

[0036] As another aspect of the present invention, a use of the above-mentioned embolic microspheres is also provided, wherein the embolic microspheres are used to adsorb one or more of doxorubicin, epirubicin, pirarubicin, irinotecan, mitoxantrone, daunorubicin, topotecan, bleomycin, oxaliplatin, gemcitabine and 5-fluorouracil.

[0037] In a preferred embodiment of the present invention, active dyes may be added to the microspheres for dyeing to enhance the visibility of the microspheres so as to facilitate user differentiation, and the active dyes include active blue and active yellow.

[0038] In a preferred embodiment according to the present invention, the wet microspheres after filtration can be sieved through stainless steel sieves with different apertures to remove unnecessary particle sizes and retain microspheres in a required size range, which can be sieved into various intervals such as 100-300 μm, 300-500 μm, 500-700 μm, 700-900 μm, etc.

[0039] The microspheres prepared according to the preferred embodiment of the present invention can be used to adsorb one or more of doxorubicin, epirubicin, pirarubicin, irinotecan, mitoxantrone, daunorubicin, topotecan, bleomycin, oxaliplatin, gemcitabine, and 5-fluorouracil.

[0040] According to the technical solution of the present invention, the following beneficial effects are achieved:

[0041] The preparation method of the present invention is relatively simple and easy to implement, can be used for industrial operation, and has universal applicability.

[0042] (1) The microspheres are highly hydrophilic and have excellent rapid drug adsorption and loading capabilities. They can adsorb more than 90% of the drug within 15 minutes after combining with the drug, and have a high drug loading capacity.

[0043] (2) It has excellent compressibility and elasticity and can quickly rebound to a spherical shape after compression.

[0044] (3) The preparation process is simple and can be completed through a single polymerization reaction without the need for grafting modification and then polymerization. The preparation conditions are mild and the cost is relatively low, which is suitable for large-scale batch production.

[0045] (4) It has good sustained-release ability and can release chemotherapy drugs at the tumor site for a long time.

[0046] (5) The drug-loaded embolic microspheres prepared by this preparation method can be sterilized by high-pressure steam at 121.3°C for 30 minutes after packaging, and the drug to be adsorbed can be added for mixed adsorption before use, thereby avoiding drug degradation during the preparation, sterilization and storage of the microspheres.

[0047] (6) During the preparation process, it was found that the drug-loaded embolic microspheres prepared using polymers with multiple sulfonic acid functional groups have better drug stability after drug adsorption than those prepared using polymers with multiple carboxyl functional groups. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a microscope picture of microspheres prepared according to Example 1 of the present invention.

[0049] Figure 2 This is a microscope picture of the microspheres prepared according to Example 1 of the present invention after adsorbing doxorubicin.

[0050] Figure 3 The in vitro drug dissolution curves of the microspheres prepared according to Examples 3 and 7 of the present invention and the commercially available microspheres. DETAILED DESCRIPTION

[0051] For a better understanding of the present invention, the embolic microspheres prepared by the present invention are further described below by comparing the relevant performance test data of the specific examples and control examples with the literature report data of similar marketed products. The examples listed are only exemplary and do not constitute any limitation to the scope of the present invention.

[0052] Embodiment 1:

[0053] Add 0.9g of cellulose acetate butyrate to 100ml of butyl acetate, stir and dissolve to form an oil phase. Dissolve 3g of polyvinyl alcohol (molecular weight is ~200000 Dalton) and 1g of sodium polyacrylate (molecular weight is ~150000 Dalton) in 30g of purified water, stir and mix evenly, and add concentrated hydrochloric acid solution to adjust the pH value to form an aqueous phase. Mix the aqueous phase and the oil phase by a stirrer at a stirring speed of 350rpm to form an oil-in-water emulsion. Add 0.2ml of glutaraldehyde aqueous solution (50% Wt), react for 2 hours, then add 0.4ml of glutaraldehyde aqueous solution (50% Wt) to the reaction system, react for 2 hours, add 0.6ml of glutaraldehyde aqueous solution (50% Wt) again, and the reaction ends after 2 hours. Filter the microspheres, and use butyl acetate, ethyl acetate and acetone to wash them several times, and obtain the dry microspheres after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10ml of wet microspheres, weigh 0.1g of reactive blue 4 and dissolve it in 20ml of water, weigh 0.08g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. The microspheres were wet-screened through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and screen into the range of 100-300μm. The water content of the microspheres was measured to be 95.6%, and the elastic modulus was 87.2Pa.

[0054] Embodiment 2:

[0055] 3.2g of cellulose acetate butyrate was added to 180ml of butyl acetate, stirred and dissolved to form an oil phase. 5.5g of polyvinyl alcohol (molecular weight is ~100000 Dalton) and 1g of sodium polyacrylate (molecular weight is ~150000 Dalton) were dissolved in 45g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 350rpm to form an oil-in-water emulsion. 0.6ml of glutaraldehyde aqueous solution (50% Wt) was added, and after reacting for 2 hours, 0.6ml of glutaraldehyde aqueous solution (50% Wt) was added to the reaction system. After reacting for 2 hours, 1.2ml of glutaraldehyde aqueous solution (50% Wt) was added again. After 2 hours, the reaction was terminated. The microspheres were filtered and washed with butyl acetate, ethyl acetate and acetone for several times, and the dry microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10ml of wet microspheres, weigh 0.1g of reactive blue 4 and dissolve it in 20ml of water, weigh 0.08g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. The microspheres were wet-screened through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and screen into 100-300μm intervals. The water content of the microspheres was measured to be 92.2%, and the elastic modulus was 92.2Pa.

[0056] Embodiment 3:

[0057] 14.2g of Tween 80 was added to 520ml of butyl acetate, stirred and dissolved to form an oil phase. 1.1g of polyvinyl alcohol (molecular weight of ~250000 Dalton) and 1.0g of sodium polyacrylate (molecular weight of ~200000 Dalton) were dissolved in 27g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH value to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 500rpm to form an oil-in-water emulsion. 0.6ml of glutaraldehyde aqueous solution (50% Wt) was added, and the reaction was terminated after stirring for 6 hours. The microspheres were filtered and washed several times with butyl acetate, ethyl acetate and acetone successively, and the dry microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10 ml of wet microspheres, weigh 0.1 g of reactive blue 4 and dissolve it in 20 ml of water, weigh 0.08 g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10 ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. Wet-screen the microspheres through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and screen into 100-300 μm intervals. The water content of the microspheres is measured to be 93.2%, and the elastic modulus is 75.2 Pa.

[0058] Embodiment 4:

[0059] 4.3g of cellulose acetate butyrate was added to 160ml of butyl acetate, stirred and dissolved to form an oil phase. 3.0g of polyvinyl alcohol (molecular weight of ~150000 Dalton) and 1.0g of sodium polyacrylate (molecular weight of ~150000 Dalton) were dissolved in 35g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH value to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 350rpm to form an oil-in-water emulsion. 0.7ml of glutaraldehyde aqueous solution (50% Wt) was added, and the reaction was terminated after stirring for 6 hours. The microspheres were filtered and washed several times with butyl acetate, ethyl acetate and acetone successively, and the dry microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and washed repeatedly with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10 ml of wet microspheres, weigh 0.1 g of reactive blue 4 and dissolve it in 20 ml of water, weigh 0.08 g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10 ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. Wet-screen the microspheres through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and screen into 100-300 μm intervals. The water content of the microspheres is measured to be 97.1%, and the elastic modulus is 102.2 Pa.

[0060] Embodiment 5:

[0061] 3.2g of cellulose acetate butyrate was added to 90ml of butyl acetate, stirred and dissolved to form an oil phase. 2.0g of polyvinyl alcohol (molecular weight of ~150000 Dalton) and 1.0g of polyacrylic acid (molecular weight of ~150000 Dalton) were dissolved in 45g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH value to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 350rpm to form an oil-in-water emulsion. 1.2ml of glutaraldehyde aqueous solution (50% Wt) was added, and the reaction was terminated after stirring for 6 hours. The microspheres were filtered and washed several times with butyl acetate, ethyl acetate and acetone successively, and the dry microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10 ml of wet microspheres, weigh 0.1 g of reactive blue 4 and dissolve it in 20 ml of water, weigh 0.08 g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10 ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. Wet sieve the microspheres through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and sieve into the range of 100 to 300 μm. The water content of the microspheres is measured to be 92.6%, and the elastic modulus is 162.8 Pa.

[0062] Embodiment 6:

[0063] 9.1g of cellulose acetate butyrate was added to 200ml of butyl acetate, stirred and dissolved to form an oil phase. 1.0g of polyvinyl alcohol (molecular weight of ~150000 Dalton) and 0.6g of sodium polyvinyl sulfonate (molecular weight of ~300000 Dalton) were dissolved in 40g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH value to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 350rpm to form an oil-in-water emulsion. 0.75ml of glutaraldehyde aqueous solution (50% Wt) was added, and the reaction was terminated after stirring for 6 hours. The microspheres were filtered and washed several times with butyl acetate, ethyl acetate and acetone successively, and the dry microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10 ml of wet microspheres, weigh 0.1 g of reactive blue 4 and dissolve it in 20 ml of water, weigh 0.08 g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10 ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. Wet sieve the microspheres through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and sieve into the range of 100 to 300 μm. The water content is measured to be 92.5%, and the elastic modulus is 173.2 Pa.

[0064] Embodiment 7:

[0065] 5.3g of cellulose acetate butyrate was added to 200ml of butyl acetate, stirred and dissolved to form an oil phase. 1.0g of polyvinyl alcohol (molecular weight of ~250000 Dalton) and 5.0g of sodium polystyrene sulfonate (molecular weight of ~1000000 Dalton) were dissolved in 45g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH value to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 350rpm to form an oil-in-water emulsion. 0.6ml of glutaraldehyde aqueous solution (50% Wt) was added, and the reaction was terminated after stirring for 6 hours. The microspheres were filtered and washed several times with butyl acetate, ethyl acetate and acetone successively, and the dry microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10 ml of wet microspheres, weigh 0.1 g of reactive blue 4 and dissolve it in 20 ml of water, weigh 0.08 g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10 ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. Wet sieve the microspheres through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and sieve into the range of 100 to 300 μm. The water content is measured to be 94.2%, and the elastic modulus is 154.62 Pa.

[0066] Embodiment 8:

[0067] 2.6g of cellulose acetate butyrate was added to 180ml of butyl acetate, stirred and dissolved to form an oil phase. 1.0g of polyvinyl alcohol (molecular weight of ~150000 Dalton) and 2.0g of sodium polystyrene sulfonate (molecular weight of ~1000000 Dalton) were dissolved in 40g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH value to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 350rpm to form an oil-in-water emulsion. 0.9ml of glutaraldehyde aqueous solution (50% Wt) was added, and the reaction was terminated after stirring for 6 hours. The microspheres were filtered and washed several times with butyl acetate, ethyl acetate and acetone successively, and the dry microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10 ml of wet microspheres, weigh 0.1 g of reactive blue 4 and dissolve it in 20 ml of water, weigh 0.08 g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10 ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. Wet-screen the microspheres through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and screen into 100-300 μm intervals, and measure the water content to be 90.3% and the elastic modulus to be 85.3 Pa.

[0068] Comparative Example 1

[0069] 3.2g of cellulose acetate butyrate was added to 180ml of butyl acetate, stirred and dissolved to form an oil phase. 6.5g of polyvinyl alcohol (molecular weight is ~100000 Dalton) and 1g of sodium polyacrylate (molecular weight is ~150000 Dalton) were dissolved in 45g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH value to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 350rpm to form an oil-in-water emulsion. 0.6ml of glutaraldehyde aqueous solution (50% Wt) was added, and after reacting for 2 hours, 0.6ml of glutaraldehyde aqueous solution (50% Wt) was added to the reaction system again. After reacting for 2 hours, 1.2ml of glutaraldehyde aqueous solution (50% Wt) was added again. After 2 hours, the reaction was terminated. The microspheres were filtered and washed with butyl acetate, ethyl acetate and acetone for multiple times, and the dry microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10ml of wet microspheres, weigh 0.1g of reactive blue 4 and dissolve it in 20ml of water, weigh 0.08g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. The microspheres were wet-screened through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and screen into 100-300μm intervals. The water content was measured to be 82.6% and the elastic modulus was 386.1Pa.

[0070] In this embodiment, the molar ratio of the hydrophilic polyhydroxy polymer material to the polyacid ion-containing polymer material is 14:1. The high content of PVA in the microspheres increases the rigidity of the microspheres, reduces the water content, and weakens the elasticity, which is not conducive to embolization.

[0071] Comparative Example 2

[0072] 2.6g of Tween 80 was added to 180ml of butyl acetate, stirred and dissolved to form an oil phase. 1.1g of polyvinyl alcohol (molecular weight of ~250000 Dalton) and 1.0g of sodium polyacrylate (molecular weight of ~200000 Dalton) were dissolved in 27g of purified water, stirred and mixed evenly, and concentrated hydrochloric acid solution was added to adjust the pH value to form an aqueous phase. The aqueous phase and the oil phase were mixed by a stirrer at a stirring speed of 500rpm to form an oil-in-water emulsion. 1.4ml of glutaraldehyde aqueous solution (50% Wt) was added, and the reaction was terminated after stirring for 6 hours. The microspheres were filtered and washed several times with butyl acetate, ethyl acetate and acetone successively, and the dried microspheres were obtained after vacuum drying. The dried microspheres were soaked and stirred in pure water for 1 hour, filtered and repeatedly washed with water, and soaked in 0.5M sodium hydroxide solution for 10 minutes and then washed with water. In addition, the microspheres were dyed with reactive blue 4 to enhance the visibility of the microspheres. Take 10 ml of wet microspheres, weigh 0.1 g of reactive blue 4 and dissolve it in 20 ml of water, weigh 0.08 g of sodium hydroxide and dissolve it in the reactive blue aqueous solution, mix the solution with 10 ml of microspheres and stir after fully dissolving, continue dyeing for 1 hour, filter and wash with purified water, boil the wet microspheres in pure water for 20 minutes, filter and collect, and obtain embolic microspheres for injection. Wet sieve the microspheres through a stainless steel sieve to obtain embolic microspheres with different particle size distributions, remove unnecessary particle sizes, and sieve into the range of 100 to 300 μm. The water content is measured to be 78.3%, and the elastic modulus is 428.3 Pa.

[0073] In this embodiment, the molar ratio of the crosslinking agent to the hydrophilic polyhydroxy polymer is 1:3.36. The rigidity of the microspheres prepared by using too much crosslinking agent is significantly increased, while the water content is affected, resulting in weakened elasticity. The poor elastic deformation ability of the microspheres is not conducive to embolization.

[0074] Commercially available products:

[0075] Commercially available products: DCBead, 100-300μm, Biocompatibiles UK Limited.

[0076] Microsphere drug loading test

[0077] 10 mg of doxorubicin hydrochloride was accurately weighed and dissolved in a 4 mL pure water vial (concentration of 2.5 mg / mL), and pirarubicin hydrochloride solution (concentration of 2.5 mg / mL) and epirubicin hydrochloride solution (concentration of 2.5 mg / mL) were prepared in the same way. 200 mg of wet microspheres with a particle size range of 100-300 μm prepared in Example 1-8 were weighed, and then the clear water was removed and added to the doxorubicin solution, and the microspheres were gently shaken to be evenly soaked in the solution. 10 uL of supernatant was sampled regularly at 10, 15, 20, and 30 minutes after the microspheres were added, and diluted in 10 mL pure water. The concentration of doxorubicin was determined by reverse phase high performance liquid chromatography (C18, 150x4.6mm) using an ultraviolet detector at a detection wavelength of 480nm and a liquid mobile phase containing 30% (v / v) acetonitrile and 0.1% (v / v) trifluoroacetic acid in water. The results are shown in Table 1. The calculation formula for drug loading is:

[0078]

[0079] Table 1 Microsphere drug loading results

[0080] sample 10min 15min 20min 30min Commercially available product (doxorubicin) 35 56 74 82 Example 1 (doxorubicin) 78 95 98 99 Example 1 (Epirubicin) 76 93 97 99 Example 1 (Pirubicin) 78 93 96 99 Example 2 (doxorubicin) 73 92 96 99 Example 3 (doxorubicin) 75 96 98 99 Example 4 (doxorubicin) 78 97 99 99 Example 5 (doxorubicin) 63 91 94 97 Example 6 (doxorubicin) 57 90 95 97 Example 7 (doxorubicin) 63 90 92 96 Example 8 (doxorubicin) 77 97 99 99 Example 8 (Epirubicin) 77 95 98 99 Example 8 (Pirubicin) 79 96 98 99

[0081] In vitro dissolution test of microsphere drugs

[0082] Take the above-mentioned Example 3 and Example 7 microspheres loaded with doxorubicin and place them in 500mL of release medium. The release medium is a 0.9% sodium chloride buffer containing 10mM morpholineethanesulfonic acid and a pH of 6.0. The microspheres are stirred in the dark (150rpm) in the release medium at 37°C, and 0.5mL of the supernatant is sampled at 1hr, 2hr, 3hr, 4hr, 18hr, 24hr, and 48hr time points, and an equal amount of release medium is immediately supplemented. The concentration of doxorubicin in the release medium is analyzed by the above-mentioned microsphere drug loading experiment HPLC method (see figure). The calculation formula for the in vitro release of the drug is:

[0083]

[0084] According to the release results, the microspheres prepared in Example 3 and Example 7 released more than 80% of the drug at 48 hours after loading doxorubicin.

[0085] Stability evaluation test after drug loading into microspheres

[0086] The microspheres were immediately stored at 2-8°C in the dark for 14 days after loading the drug, and samples were taken on the 7th and 14th days after loading the drug, and the changes in the main peak and impurity peak of doxorubicin were detected by HPLC. The microspheres loaded with doxorubicin were placed in 500 mL of eluent, which was a mixed solution of 250 mL of 20% w / v potassium chloride and 250 mL of anhydrous ethanol, stirred in the dark for 7 hours, and the supernatant was analyzed by HPLC. The results are shown in Table 2.

[0087] Table 2 HPLC detection of the main peak and impurity peak of doxorubicin

[0088]

[0089] According to the test results, the microspheres prepared by using polyionic polymers with sulfonic acid groups have better stability after adsorbing doxorubicin than polyionic polymers with carboxyl groups, and the degradation of doxorubicin in the microspheres within 14 days is less than 1%.

[0090] Determination of the compressibility of microspheres

[0091] Use a physical property analyzer (SMSTA.XTPlusC) with a 5Kg sensor, and cooperate with a high-magnification camera and video synchronization device (VC / CSS) to confirm the placement status of the microspheres, and evaluate the rigidity of the microspheres by measuring the elastic modulus of the microspheres. The elastic modulus can be regarded as an indicator of the ease of compression deformation of the material. The larger the value of the elastic modulus, the greater the stress of the material undergoing a certain elastic deformation. Therefore, the greater the rigidity, the smaller the elastic deformation. A flat single layer of microspheres is placed on the test bench, using a 5mm diameter circular probe, a speed of 1mm / s, a sensing force of 5g, and the gradient when the sample is compressed by 20% is the elastic modulus of the sample.

[0092] According to the test results, the elastic modulus values ​​of the microspheres prepared by the methods of Examples 1-8 are similar to those of commercially available products, and the microspheres have good elasticity, which ensures that the microspheres can adapt to the morphology of blood vessels to the greatest extent and can fully embolize and adhere to blood vessels.

[0093] Determination of water content of microspheres

[0094] Measure the moisture content in the microspheres, and measure the difference between the weight of the hydrated microspheres and the weight of the dehydrated microspheres by gravimetric analysis. Take the microspheres prepared in the above example, remove the moisture on the surface of the microspheres and weigh them to obtain the weight of the hydrated microspheres. Dehydrate them in an oven at 80°C for 24 hours, and then re-weigh every 8 hours until the mass of the microspheres is observed to no longer decrease. The formula for calculating the moisture content of the microspheres is:

[0095]

Claims

1. A method for preparing negatively charged embolic microspheres, characterized in that: The following steps are involved: A) dissolving a hydrophilic polyhydroxy polymer and a polymer containing polyacid ions in water, stirring uniformly, to obtain an aqueous phase; B) dissolving the dispersant in an organic solvent and stirring the mixture to obtain an oil phase; C) adding the aqueous phase to the oil phase for dispersion to obtain a mixed emulsion, adding a crosslinking agent to the mixed emulsion once or several times and stirring to obtain microspheres; D) washing and filtering the microspheres obtained in step C), After the aqueous phase is prepared in step A) or after the mixed emulsion is obtained in step C), the pH is adjusted to be acidic.

2. The method according to claim 1, characterized in that The molar ratio of the hydrophilic polyhydroxy polymer to the polymer containing polyacid ions is 0.8:1 to 12:

1.

3. The method according to claim 2, characterized in that The molar ratio of the hydrophilic polyhydroxy polymer to the polymer containing polyacid ions is 2.3:1 to 12:

1.

4. The method according to claim 1, characterized in that: The total weight of the hydrophilic polyhydroxy polymer and the polymer containing polyacid ions accounts for 4% to 15% of the total weight of the water phase.

5. The method according to claim 1, characterized in that: The molar ratio of the crosslinking agent to the hydrophilic polyhydroxy polymer is 1:4 to 1:

19.

6. The method according to claim 1, characterized in that The volume ratio of water in the aqueous phase to the organic solvent in the oil phase is 1:1.5 to 1:

20.

7. The method according to claim 1, characterized in that The organic solvent for preparing the oil phase is one or a mixture of butyl acetate, ethyl acetate and n-heptane.

8. The method according to claim 1, characterized in that The mass percentage of the dispersant in the oil phase is 0.8% to 5.0%.

9. The method according to claim 1, characterized in that: The hydrophilic polyhydroxy polymer is polyvinyl alcohol.

10. The method according to claim 9, characterized in that The molecular weight of the polyvinyl alcohol is 20 to 600 kilodaltons.

11. The method according to claim 1, characterized in that: The polymer containing polyacid ions is a polymer containing polycarboxyl functional groups and / or a polymer containing polysulfonic functional groups.

12. The method according to claim 11, characterized in that The polymer containing multiple carboxyl functional groups is polyacrylic acid and / or its salt, polymethacrylic acid and / or its salt, and the polymer containing multiple sulfonic functional groups is poly(p-styrene sulfonic acid) and / or its salt, poly(vinyl sulfonic acid) and / or its salt.

13. The method according to claim 12, characterized in that The polymer containing multiple carboxyl functional groups is one or more of sodium polyacrylate (PAANa), partially neutralized sodium polyacrylate, polyacrylic acid (PAA), sodium polymethacrylate and polymethacrylic acid, and the molecular weight of a single type of polymer is 10 to 600 kilodaltons, wherein the mass ratio of acrylic acid to sodium acrylate in the partially neutralized sodium polyacrylate is 2:8 to 8:2; the polymer containing multiple sulfonic functional groups is one or more of sodium poly(p-styrene sulfonate), poly(p-styrene sulfonic acid), sodium poly(ethylene sulfonate) and poly(ethylene sulfonic acid), and the molecular weight of a single type of polymer is 20 to 2000 kilodaltons.

14. The method according to claim 1, characterized in that The cross-linking agent is an aldehyde compound.

15. The method according to claim 14, characterized in that The cross-linking agent is glyoxal and / or glutaraldehyde.

16. The method according to claim 1, characterized in that The dispersant is one or a combination of Span 80, Tween 80, cellulose acetate and cellulose acetate butyrate.

17. The method according to claim 1, characterized in that In step C), the aqueous phase is dispersed in the oil phase by shearing or stirring, wherein the stirring speed is 50 rpm to 1000 rpm.

18. The method according to claim 1, characterized in that After the aqueous phase is prepared in step A) or after the mixed emulsion is obtained in step C), one or more of hydrochloric acid, sulfuric acid and acetic acid are added to adjust the pH to 3-5; the microspheres collected by filtration in step D) are washed with butyl acetate and ethyl acetate in turn, and then washed with acetone or ethanol, and then vacuum dried to obtain dry microspheres, the dry microspheres are soaked in pure water and filtered, then soaked in sodium hydroxide solution and filtered with water, and then filtered, sieved and collected after stirring in boiling water.

19. Negatively charged embolic microspheres prepared according to the method of any one of the preceding claims.

20. A use of the negatively charged embolic microspheres according to claim 19, characterized in that: The embolic microspheres are used to adsorb one or more of doxorubicin, epirubicin, pirarubicin, irinotecan, mitoxantrone, daunorubicin, topotecan, bleomycin, oxaliplatin, gemcitabine and 5-fluorouracil.